TRANSIENT MOTION SIMULATION AND STRESS ANALYSIS OF RECIPROCATING COMPRESSOR VALVE - WANG Yao; ZHANG JinJie; LIU JinNan; YAO ZiYun; JIANG ZhiNong (Jixie qiangdu)
Reciprocating compressor has many moving and damageable parts in which valve is the most frequently damaged component. A mathematical model of the valve movement was established according to its structure and motion characteristics.MATLAB and ANSYS software were used to study the transient motion law and the dynamic stress distribution of mesh valve.Then the impact of spring stiffness and transition arc on valve’s stress distribution was discussed. The results show that the stress generated by deformation is much greater than the impact stress. Maximum elastic deformation occurs in two thin elastic arms in which maximum equivalent stress generated. Changing the spring stiffness and the curvature of the transition arc can effectively reduce the stress and extend the life of the mesh valve. The results of the analysis have important theoretical significance for valve design optimization and the improvement of valve life.